A series of selenium-containing non-fullerene acceptors with side chain engineering for organic solar cells. (November 2022) - Oh, Juhui; Park, Hye Yeon; Kim, Ju-Hyeon; Chen, Shuhao; Lee, Sanseong; Kim, Jaeyoung; Song, Xuyao; Kang, Hongkyu; Jang, Soo-Young; Kwon, Soon-Ki; Kim, Yun-Hi; Lee, Kwanghee
Abstract: Non-fullerene acceptors (NFAs) have been crucial in improving the efficiency of organic solar cells (OSCs) due to their attractive properties, such as strong light-harvesting ability, easily tunable energy levels, and high crystallinity. Nevertheless, general NFAs have limited light absorption, and studies on the design of NFAs that can absorb a broad range of the solar spectrum and that offer complementary absorption to that of donors should be conducted. Because selenium, a chalcogen element, can induce strong intermolecular Se⋯Se interactions, planarity, and extended effective conjugated length in OSC materials, NFAs with selenium usually exhibit redshifted absorption. Here, we synthesized a series of selenium-containing non-fullerene acceptors with different inner alkyl chain lengths, named Se-Y6-BO (2, 2'-((2Z, 2′Z)-((12, 13-bis(2-butyloctyl)-3, 9-dinonyl-12, 13-dihydroselenopheno[2″, 3'':4′, 5']thieno[2′, 3':4, 5]pyrrolo[3, 2-g]selenopheno[2′, 3':4, 5]thieno [3, 23, 2-b] [1, 2, 5]thiadiazolo [3, 43, 4-e]indole-2, 10-diyl)bis(methanylylidene))bis(5, 6-dichloro-3-oxo-2, 3-dihydro-1H-indene-2, 1-diylidene))dimalononitrile) and Se–Y6-HD (2, 2'-((2Z, 2′Z)-((12, 13-bis(2-hexyldecyl)-3, 9-dinonyl-12, 13-dihydroselenopheno[2″, 3'':4′, 5']thieno[2′, 3':4, 5]pyrrolo[3, 2-g]selenopheno[2′, 3':4, 5]thieno [3, 23, 2-b] [1, 2, 5]thiadiazolo [3, 43, 4-e]indole-2, 10-diyl)bis(methanylylidene))bis(5, 6-dichloro-3-oxo-2, 3-dihydro-1H-indene-2, 1-diylidene))dimalononitrile). The optical absorption of two selenium-containing NFAs was redshifted compared with that of Y6 due to the effect of selenium atoms in the backbone. The PM6:Se-Y6-BO-based devices achieved a power conversion efficiency (PCE) of 13.8% with an open-circuit voltage ( V OC ) of 0.81 V, short-circuit current density ( J SC ) of 24.4 mA cm −2, and a fill factor of 0.70. Similarly, the OSCs based on PM6:Se–Y6-HD achieved a PCE of 13.6% and a J SC of 23.7 mA cm −2 . Highlights: A series of selenium-substituted non-fullerene acceptors with side chain engineering were synthesized for organic photovoltaics. Two new selenium-containing non-fullerene acceptors, named Se-Y6-BO and Se–Y6-HD, achieved the best power conversion efficiency of 13.8% and 13.6%, respectively.